The impact of the extent of surgical resection on survival of gastric cancer patients - Angelov, Kostadin Georgiev (Onco Targets Ther, 2016)
OBJECTIVE: The aim of this study was to examine the significance of the extent of gastric resection on the postoperative and overall gastric cancer survival. BACKGROUND: Resection with clean margins (4 cm or more) is widely accepted as the standard-ized goal for radical treatment of gastric cancer according to current guidelines, while the type of resection (subtotal or total) is still a matter of debate. PATIENTS AND METHODS: The study included 155 patients diagnosed and treated in the Department of Surgery, Aleksandrovska University Hospital between January 2005 and December 2014. In order to determine the significance of the resection volume, we excluded from the study 54 patients receiving palliative intervention or staging exploratory laparoscopy. The remaining 101 patients were divided into two groups based on the volume of the performed gastric resection (total and subtotal) and compared based on overall survival and perioperative mortality. We also investigated the 3-year survival in the two groups as well as the overall survival only in the subgroup of patients with D2 lymphadenectomy. RESULTS: We could not determine any statistically significant difference in overall survival and 3-year survival (P=0.990) based on the extent of surgical resection (P=0.824) or perioperative mortality. The statistical analysis on patients with D2 lymph node dissection only did not show significance for overall survival. CONCLUSION: Our study shows no difference in safety and long-term survival rate of patients with gastric carcinoma based on the volume of stomach resection. Comparison with other studies also shows no difference in survival based on volume of the resection.